PUJIAN DALAM BAHASA INGGRIS DAN BAHASA MONGONDOW (SUATU ANALISIS KONTRASTIF) - Sengkey, Stenla; Pelealu, Hetty; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research entitled â€œCompliments in English and Mongondow Language: A Contrastive Analysisâ€. The objectives of this research are to identify, classify, and to contrast the topics and responses of compliments in English and Mongondow languages. This research uses a descriptive method. The data of compliments in English were collected from films entitled Forever my Girl (2018) and A Star is Born (2018), while the data of compliments in Mongondow language were collected from observation of conversations among people who live in Kopandakan II and can speak Mongondow language well. The writer uses the theory of Wolfson in Richards and Shcmidt (1986) to identifi, classifi, and describe the data about the topics of compliment and the responses of compliment of both languages. The writer uses Ladoâ€™s theory (1957) to make a contrastive analis of both languages in finding out the similarities and differences of compliments and its responses in English and Mongondow language. This result shows that the topics of compliment in Mongondow language are personal attribute, possession, children, pet, accomplishment, and change in appearance, while in English Language are personal attribute, possession, children, pet, accomplishment, and change in appearance. The responses of compliment in Mongondow language are acceptance, agreement, rejection, shift, and return and the responses of compliment in English Language are acceptance, agreement, rejection, shift, and return. The similarities of the topics of compliment in Mongondow language and English language which are found namely personal attribute, possession, children, pet, accomplishment, and change in appearance, and the compliment responses in Mongondow language and English language namely acceptance, agreement, rejection, shift, and return. The differences of both languages namely the topics of compliment in Mongondow language is found about plants while in English language isnâ€™t, while the responses of compliment in Mongondow language has shy while smilling, and laugh while in English language. The adjectival words which are used in English Language namely beautiful, proud, the best, ravishing, great, excited, cute, good, lucky, soft, kind, nice, amazing, very good, well, smells good, perfect, and awesome while in Mongondow language namely moâ€™ jago, moâ€™ lawak, moâ€™ sopan, moâ€™ bagu, moâ€™ pandoi, totok moâ€™ rajing, aidon no lunat, noâ€™ lebeh pasung, no lebeh lantut, and ontongon moâ€™ muda. The verbal words used in Compliments namely like and love, and in Mongondow language moâ€™ ibog. The adjectival used frequently in English Language are beautiful, good, and great while in Mongondow language namely noâ€™ lebeh pasung and moâ€™ bagu.Keywords: Compliment, English and Mongondow Language, Contrastive Analysis